The use of seaweed in daily diets as a source of nutrientes - García-Oliveira, Paula (2019)
Seaweed plays an important role in the biosphere being responsible for most of the production in aquatic ecosystems [1]. Although commonly consumed since ancient times in Asia, their consumption has been increasing in Europe and North America [2]. These species are known for their excellent nutritional value, especially as a protein sources and low lipid and caloric content. In addition, they are rich in several bioactive compounds, such as vitamins, essential fatty acids and phenolic compounds, providing important health benefits to consumers [3]. This work aims to determine ash, proteins, fat, carbohydrates and energy contents, as also the composition in free sugars, organic acids and fatty acids of some seaweeds species, namely Himanthalia elongate L., S.F. Gray; Laminaria ochroleuca Bach.Pyl.; Saccharina latissima L.; Porphyra sp. C.Agardh; Palmaria palmata (L.) Kuntze, and Undaria pinnatifida (Harvey) Suringar. The nutritional aspects were determined using official methodologies for food analysis, while free sugars were identified by HPLC-RI, organic acids by UPFLC-PDA and fatty acids by GC-FID. Proteins stood out as the main macronutrients present, with values that oscillated between 6 and 30 g/100 g of dry weight (dw) for S. latissima and Porphyra sp., respectively. On the other hand, a low lipid content was evident in all the studied seaweed species with values below 1 g/100 g dw, as well as low carbohydrates’ content. The energy values ranged from 218 and 370 kcal/100 g dw for L. ochrouleuca and Porphyra sp, respectively. Furthermore, several compounds of interest were identified, namely free sugars and organic acids, in this case being oxalic acid the only molecule present in all species. Saturated, unsaturated and polyunsaturated fatty acids were also determined, showing a clear heterogeneity of concentrations depending on the species. The present study demonstrates the high potential of these seaweed species as an alternative source of non-animal protein, as well as some molecules with bioactive properties. Thus, the incorporation of this food into the daily diet will contribute for the improvement of a number of functionalities.